Prevalence, pattern, and predictors of WPV against medical interns in Southwest Nigeria: a cross-sectional study - Nicholas Aderinto; Gbolahan Olatunji; Peter Olaniyi; Samson Afolabi; Kamil Ajagbe; Ismaila Ajayi Yusuf; Deborah Ojo; Samuel Olatunji; Adedamola Awodun; Tsele Toritseju; Kadiri A. Olamide; Grace Ijitade; et al. (Annals of Medicine)
Background Workplace violence (WPV) is a significant occupational hazard threatening the safety and well-being of medical interns in Nigeria. Despite its critical impact, there is a notable research gap regarding the prevalence, patterns, and influencing factors of WPV among medical interns in Southwest Nigeria. This study aims to fill this gap by investigating these aspects.Methods This cross-sectional study utilized online questionnaires to collect data from 379 medical interns at ten hospitals in Southwest Nigeria. The data were analyzed using descriptive statistics and logistic regression.Results The study found that 62.5% of medical interns had experienced WPV. Verbal abuse was the most common type of violence (63.3%), followed by threats (50.4%), physical assault (24.3%), verbal sexual harassment (13.2%), and physical sexual abuse (2.6%). The primary perpetrators were patients’ relatives (81.9%) and patients (61.2%). WPV predominantly occurred in the afternoon (68.8%) and in emergency rooms (70.5%). The primary triggers were long waiting times (64.6%) and unmet patient needs (54.9%). Female interns had higher odds of experiencing WPV, with an adjusted odds ratio of 3.01 (95% CI: 0.82–11.03, p = 0.01) than their male counterparts.Conclusion WPV is prevalent among medical interns in Southwest Nigeria, with patients as the main perpetrators. Healthcare organizations must implement measures such as promoting a culture of respect, establishing zero-tolerance policies, training interns to recognize and address WPV, and providing support for victims.